Global trends and future perspectives in autism spectrum disorder and gut microbiota research: a comprehensive bibliometric analysis - Liu, Guojun; Chen, Linzi; Guan, Maosen; Xiao, Ningkun (Frontiers in Neuroscience, 2026)
BackgroundAutism spectrum disorder (ASD) is a heterogeneous neurodevelopmental condition. Increasing studies examine whether gut microbiota alterations and the gut–brain axis are linked to ASD-relevant phenotypes. As the literature expands rapidly, a quantitative mapping is needed to clarify influential work and evolving themes.ObjectiveTo map global research on ASD and the gut microbiota, identify major contributors and knowledge bases, and characterize thematic evolution and emerging fronts.MethodsWe analyzed 1,391 English-language articles and reviews indexed in the Web of Science Core Collection (1999–2024). CiteSpace, VOSviewer, and R were used to evaluate publication trends, collaboration networks, co-citation structure, keyword clustering, and burst detection.ResultsPublication output increased slowly before 2010 and accelerated after 2018. The United States and China were leading contributors and key collaboration hubs. The co-citation core was anchored by landmark experimental and translational studies, including work on microbiome-to-behavior links and microbiome-targeted interventions. Keyword clustering and timeline views highlighted three prominent thematic directions: fecal microbiota transplantation, Rett syndrome, and maternal immune activation. Recurrent and burst keywords emphasized the gut–brain axis, short-chain fatty acids, gastrointestinal symptoms, and oxidative stress. Recent burst terms, including obesity, major depressive disorder, and glutamate, suggest increasing connections to metabolic and broader psychiatric dimensions.ConclusionASD–microbiome research has shifted from descriptive comparisons toward mechanism-oriented and intervention-relevant questions. Future progress will benefit from standardized protocols, longitudinal designs, and multi-omics integration, together with rigorously designed trials to evaluate microbiome-targeted strategies.